2019
DOI: 10.1101/19013623
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

rs641738C>T nearMBOAT7is positively associated with liver fat, ALT, and histological severity of NAFLD: a meta-analysis

Abstract: Background & Aims A common genetic variant near MBOAT7 (rs641738C>T) has been previously associated with hepatic fat and advanced histology in non-alcoholic fatty liver disease (NAFLD), however, these findings have not been consistently replicated in the literature. We aimed to establish whether rs641738C>T is a risk factor across the spectrum of NAFLD and characterise its role in the regulation of related metabolic phenotypes through meta-analysis. Methods We performed meta-analysis of studies with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Data were collected from 1047.265 subjects, of whom 8303 had liver biopsies, and displayed a correlation between the T minor allele and hepatic fat deposition, ALT levels, and advanced stages of NAFLD, such as fibrosis and HCC. In particular, carriers of the rs641738 variant show a 30% risk of developing HCC compared to non-carriers [ 203 ]. Physiologically, MBOAT7 localizes on MAMs and mediates phosphatidylinositol (PI) acyl-chain remodeling in the Land’s cycle.…”
Section: The Link Among Nafld Mitochondrial Dysfunction and Hcc: The Relevance Of Geneticsmentioning
confidence: 99%
“…Data were collected from 1047.265 subjects, of whom 8303 had liver biopsies, and displayed a correlation between the T minor allele and hepatic fat deposition, ALT levels, and advanced stages of NAFLD, such as fibrosis and HCC. In particular, carriers of the rs641738 variant show a 30% risk of developing HCC compared to non-carriers [ 203 ]. Physiologically, MBOAT7 localizes on MAMs and mediates phosphatidylinositol (PI) acyl-chain remodeling in the Land’s cycle.…”
Section: The Link Among Nafld Mitochondrial Dysfunction and Hcc: The Relevance Of Geneticsmentioning
confidence: 99%
“…Data were collected from 1047.265 subjects, of whom 8303 had liver biopsies, and displayed a correlation between the T minor allele and hepatic fat deposition, ALT levels and advanced stages of NAFLD, like fibrosis and HCC. In particular, carriers of the rs641738 variant show the 30% risk to develop HCC compared to non-carriers [207].…”
Section: The Impact Of Hypoxia On Hepatic Metabolic Reprogramming Andmentioning
confidence: 99%
“…A recent meta‐analysis with 131,096 participants (including 4174 children) out of which 7692 subjects had liver biopsy with histopathological assessment and 45,419 subjects had imagistic evaluation demonstrated that minor T allele of rs641738C > T was associated with elevated hepatic steatosis evaluated using computed tomography (CT)/magnetic resonance imaging (MRI) that was assessed by an additive genetic model (+0.05 standard deviations [95% CI: 0.01‐0.09], P = .025) 33 . Moreover, an increased risk of NAFLD (per‐allele OR: 1.09 [95% CI: 1.01‐1.17]), nonalcoholic steatohepatitis (OR: 1.11 [95% CI: 1.02‐1.21]), advanced fibrosis (OR: 1.14 [95% CI: 1.05‐1.23]) and HCC (OR: 1.43 [95% CI: 1.22‐1.67]) in adults with NAFLD was documented without any difference between Caucasians and non‐Caucasians sub‐group analysis.…”
Section: Rs641738c > T Variant Near Membrane‐bound O‐acyltransferase mentioning
confidence: 99%
“…Subsequently, multiple studies demonstrated that it is involved in the pathogenesis of several hepatic diseases including MAFLD independent of obesity, 25 as well as HCC 27 and fibrosis development in chronic viral hepatitis B and C infections 28‐31 . Nevertheless, the current literature contains conflicting data associating the genetic variant near MBOAT7 (rs641738C > T) polymorphism with an increased risk of developing MAFLD 32,33 …”
Section: Introductionmentioning
confidence: 99%